90 | ÷ | x | + | 90 | ÷ | ( | x | + | 66 5 | ) | = | 1 |
Multiply both sides of the equation by: | x |
90 | + | 90 | ÷ | ( | x | + | 66 5 | ) | × | x | = | 1 | x |
Multiply both sides of the equation by: | ( | x | + | 66 5 | ) |
90 | ( | x | + | 66 5 | ) | + | 90 | x | = | 1 | x | ( | x | + | 66 5 | ) |
90 | x | + | 90 | × | 66 5 | + | 90 | x | = | 1 | x | ( | x | + | 66 5 | ) |
90 | x | + | 90 | × | 66 5 | + | 90 | x | = | 1 | x | x | + | 1 | x | × | 66 5 |
90 | x | + | 1188 | + | 90 | x | = | 1 | x | x | + | 66 5 | x |
180 | x | + | 1188 | = | 1 | x | x | + | 66 5 | x |